MEMAHAMI KARAKTERISTIK BAHASA AL-QUR`AN DALAM PERSPEKTIF BALAGHIYAH - Mustamar, Marzuki (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2008)
The nature of language is to express that someone exists, or in other word, expressing the existence. Through the revelation Allah introduces his existence to the creature. It can also be seen from the qudsi hadists  popular among the sufi. It is said that Dawud asked to Allah, why do you create the creature? Allah answered, “I am the hidden hemisphere and I want to be known. For that reason I create the creatures so that I am known”.